Essays in experimental economics - Grigorieff, A (2018)
In the first chapter, I investigate the impact of income inequality on anti-social behaviour through an experiment. Participants are first assigned to two different kinds of groups: equality groups, where everyone is paid the same amount for performing a simple task, and inequality groups, where people receive different amounts for completing the same task. Each participant is then told that one member of their group will have the possibility of taking some of the money earned by another group member. Contrary to the predictions made by the Becker model and the Fehr-Schmidt inequity aversion model, participants in the inequality groups steal significantly less from a fellow group member with the same income as them than people in the equality groups. The second chapter, jointly written with Christopher Roth, examines the influence of economic status on pro-social behaviour using a large experiment with a representative sample of the US population. We exogenously alter people's perceived economic status by changing where they think their household stands in the US income distribution. Half of the people who over-estimated their position in the income distribution are told that they are relatively poorer than they thought. Conversely, half of those who under-estimated their position in the income distribution are informed that they are relatively richer than they thought. Then, participants play a series of four incentivised games, which measure different social preferences, such as trust, negative reciprocity, honesty and altruism. We show that individuals who learn that they are lower (resp. higher) in the income distribution than they thought become less (resp. more) satisfied with their relative position in the income distribution, but that their behaviour remains unchanged in the four behavioural games. The third chapter, co-written with Christopher Roth and Diego Ubfal, studies whether providing information about immigrants affects people's attitude towards them. First, we use a large representative cross-country experiment to show that, when people are told the share of immigrants in their country, they become less likely to state that there are too many of them. Then, we conduct two online experiments in the US, where we provide half of the participants with five statistics about immigration, before evaluating their attitude towards immigrants with self-reported and behavioural measures. This more comprehensive intervention improves people's attitude towards existing immigrants, although it does not, on average, change people's policy preferences regarding immigration. However, Republicans become more willing to increase legal immigration after receiving the information treatment.